Valuing environmental and natural resources the econometrics of non-market valuation - Haab, Timothy C., 1969-; McConnell, Kenneth E.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : E. Elgar Pub., 2002)
Non-market valuation has become a broadly accepted and widely practiced means of measuring the economic values of the environment and natural resources. In this book, the authors provide a guide to the statistical and econometric practices that economists employ in estimating non-market values.
1. Welfare economics for non-market valuation -- 2. Parametric models for contingent valuation -- 3. Distribution-free models for contingent valuation -- 4. The distribution of willingness to pay -- 5. Topics in discrete choice contingent valuation -- 6. Modeling the demand for recreation -- 7. Single site demand estimation -- 8. Site choice models -- 9. Hedonic price equations -- 10. New directions in non-market valuation.
Includes bibliographical references (p. [278]-297) and index.
Keywords: Natural resources -- Valuation; Environmental economics; Electronic books